(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Chronic glomerulonephritis (chronic nephritic syndrome) is a group of diseases heterogeneous in origin and pathomorphology, characterized by immunoinflammatory damage of the tubules, tubules and interstitium of both kidneys and progressive course, resulting in the development of nephrosclerosis and chronic renal failure.